The Influence of Taharah Behavior in Daily Life on Diarrhea Diseases - Ernyasih Ernyasih; Abul A’la Al Maududi; Nur Romdhona; Dadang Herdiansyah; Rohimi Zamzam (Indonesian Journal of Islam and Public Health, 2021)
Diarrhea is a disease characterized by a change in the stool with bowel movements 3 times a day. In 2014 the incidence of diarrhea in East Java reached 106%, in Malang Regency it reached 53,383 people (34.40%), among them were under five (in the 6-35 month age group, because children began to actively play and were at risk of infection) and the rest all ages due to the low hygiene and healthy lifestyle. The purpose of this paper is to increase public knowledge in an Islamic perspective, namely taharah against diarrhea, with preventive measures, namely Clean and Healthy Behavior (PHBS). Data obtained from literature reviews downloaded through the 5 journals regarding the relationship between behavior and diarrhea. There is a relationship between Clean and Healthy behaviors against diarrhea which is obtained from 5 public behavior journals by improving clean water facilities, providing latrines for families who do not have this access, increasing information provision to the community about good Clean and Healthy Behaviors. and true through the media and in collaboration with schools or Public Health Centre.